3 shades of blue : Miles Davis, John Coltrane, Bill Evans, and the lost empire of cool - Kaplan, James, 1951- (Penguin Press, 2024)
"From the author of the definitive biography of Frank Sinatra, the story of how jazz arrived at the pinnacle of American culture in 1959, told through the journey of three towering artists-Miles Davis, John Coltrane, and Bill Evans-who came together to create the most famous and bestselling jazz album of all time, Kind of Blue. The myth of the 60s depends on the 1950s being the before times of conformity, segregation, straightness-The Lonely Crowd and The Organization Man. This all carries some truth, but it does nothing to explain how, in 1959, the great indigenous art form, jazz, reached the height of its power and popularity, led there by a number of Black geniuses so iconic they go by one name-Monk, Mingus, Rollins, Coltrane, and above all, Miles. 1959 saw Miles, Coltrane, Bill Evans, and the other members of Miles's sextet come together to record what is widely considered the greatest jazz album of all time, and certainly the best-selling: Kind of Blue. 3 Shades of Blue is James Kaplan's magnificent account of the paths of the three giants Miles, Coltrane and Evans to the mountaintop of 1959 and their path on from there. It's a book about music, and business, and race, and heroin, and the towns that gave jazz its home, from New York and LA to Philadelphia, Chicago and Kansas City. It's an astonishing meditation on creativity and the strange hothouses that can produce its full flowering. It's a book about the great forebears of this golden age, particularly Charlie Parker, and the people, like Ornette Coleman, who would take the music down strange new paths. And it's about why this period has never been replicated, why the world of jazz most people visit is a museum to it. But above all this is a book about three very different men-their struggles, their choices, their tragedies, their greatness. Bill Evans had a gruesome downward spiral, John Coltrane took the mystic's path into a space far away from mainstream concerns. Miles had three or four sea changes in him before the end. The tapestry of their lives is, in Kaplan's hands, an American Odyssey, with no direction home. It is also a masterpiece, a book about jazz that is as big as America"--